Carbon and water relations of contrasting Arctic plants: implications for shrub expansion in West Greenland. Issue 4 (22nd April 2016) - Cahoon, Sean M. P.; Sullivan, Patrick F.; Post, Eric
Abstract: The recent expansion of deciduous shrubs is a common observation throughout the Arctic. However, we lack a complete understanding of how physiological differences between deciduous shrubs and coexisting species may confer competitive advantages to shrubs. We combined leaf gas exchange and stable isotope analyses of two important species, Betula nana and Poa pratensis, to elucidate the processes governing seasonal carbon (C) gain in West Greenland. We tested two competing hypotheses. On one hand, we anticipated the cooler, drier soils beneath the Betula canopy could result in greater drought sensitivity in this species. Alternatively, because Poa tends to occupy sites with wetter soils, we hypothesized that it may be more sensitive to drought. Our results revealed greater drought sensitivity in Poa, which displayed reductions in A max and g s during periods of high atmospheric demand and dry soils. Additionally, leaf Δ 13 C and Δ 18 O were negatively correlated in Poa, suggesting strong stomatal influence on Δ 13 C. Conversely, there was no relationship between g s and canopy or soil microclimates and no correlation between leaf Δ 13 C and Δ 18 O in Betula, indicating that variation in Δ 13 C may have been driven by variation in photosynthesis. Our results suggest that Poa is more susceptible to drought than Betula, whereas Betula was able to maintain steady, yet conservative, C gain. These differences in C‐H2 O relations may confer a competitive advantage to Betula in a warmer, drier climate.